Influence of Dentists' Attire on Patient Perceptions: Gender Differences and Social Media Impact - Gasparello, Gil Guilherme; Marques, Camila Souza; Acciaris, Fábio; Bark, Mohamad Jamal; Castilhos, Jussimar Scheffer; Barco, Agustina; Tanaka, Orlando Motohiro (European Journal of General Dentistry, 2025)
The attire and appearance of health care professionals play an important role in shaping patients' perceptions of their professionalism, confidence, and credibility. In the era of social media, where image and visual presentation are highly valued, one might question whether details such as the color of laboratory coats have changed. This study aimed to evaluate patient preferences regarding dentists' attire and its impact on their confidence and perceptions of professionalism. Additionally, the study explored gender-based differences in these responses.A total of 73 participants (38 males and 35 females; mean age 20.18 years) were enrolled. Participants were presented with images of male and female dentists wearing laboratory coats and scrubs in six colors (white, dark blue, light blue, gray, black, and green) and their visual attention was tracked using The Eye Tribe tracker and OGAMA software. Following the eye-tracking session, participants completed a questionnaire on the importance of a dentist's appearance, attire preferences, and color preferences using visual analog scale. Data were analyzed using SPSS (v.25) with descriptive statistics, Student's t-test, Pearson's chi-squared test, and validation tests (Kaiser–Meyer–Olkin = 0.682, Bartlett's p < 0.001).Participants preferred white attire (40%) over other colors, with dark blue and light blue following. Younger participants showed some interest in nontraditional attire, though white remained dominant. Gender differences were observed; females were more likely to feel uncomfortable with a dentist's attire (17.1%) compared with males (2.6%; p = 0.035). Both genders favored laboratory coats over scrubs, but no significant differences were found regarding attire preferences (p = 0.352).Traditional white attire remains the preferred choice among participants, reflecting professionalism and trust. However, gender differences in discomfort with attire suggest the need for tailored approaches in clinical settings. These findings may also have implications for social media, where the digital representation of health care professionals could shape patient expectations and preferences.
Keywords: dentists' attire; gender differences; professionalism; social media influence; eye-tracking